The Influence of Digital Literacy on Learning Effectiveness Through Classroom Management: Moderating Effect of IT Infrastructure - Debby Fransisca Muntu; Oviliani Yenty Yuliana; Zeplin Jiwa Husada Tarigan (Petra International Journal of Business Studies, 2023)
Digital Literacy is essential in the post-pandemic era. Teachers use Digital Literacy to provide learning materials, conduct the teaching process, and conduct evaluations online. However, Digital Literacy requires adequate information technology infrastructure to produce classroom management and learning effectiveness on an ongoing basis. The study used questionnaires to obtain data on Christian-based schools in Surabaya. The questionnaires were distributed to as many as 363 through a Google form, and 132 were filled out again. Data processing used partial least square. The results showed that digital literacy has an impact on classroom management. Classroom management influences learning effectiveness. Digital literacy affects learning effectiveness through classroom management. Digital Literacy has not influenced classroom management and learning effectiveness with information technology infrastructure as a moderating variable. This research provides a practical contribution for education managers to understand the adjustment of IT infrastructure to make digital literacy the basis for managing class management. In addition, teaching staff must be educated to keep abreast of technological developments to support the teaching process and improve class management. The study enriches the theory of the use of technology in education and interactional education in the classroom.